Differentiated Thyroid Cancer in Adolescents: Single Center Experience and Considerations for Surgical Management and Radioiodine Treatment - Costanza Chiapponi; Milan Janis Michael Hartmann; Boris Decarolis; Thorsten Simon; Christiane Josephine Bruns; Michael Faust; Anne Maria Schultheis; Matthias Schmidt; Hakan Alakus (Galenos Yayincilik, 2023)
INTRODUCTION: Differentiated thyroid cancer (DTC) in adolescents rare but with a favorable outcome, despite higher rates of cervical lymph node and pulmonary metastasis compared to adults. The aim of this study was to critically evaluate treatment of adolescents with DTC at a single center. METHODS: Patients receiving postoperative radioiodine treatment (RAIT) for DTC between 2005 and 2020 at our institution were screened to identify adolescents according to the World Health Organization definition (10-19 years of age). Demographics, clinico-pathological characteristics, treatment and outcome were analyzed. RESULTS: Among 1,897 DTC patients, 23 (1.3%) were adolescents with a median (range) age of 16 (10-18) years. The female to male ratio was 3.6: 1. Sixty percent had classic papillary thyroid cancer, with follicular variant in 40%, which was higher than previously reported (15-25%) for this age group. pT-status was pT1 in 9 (39.2%), pT2 in 8 (34.8%), pT3 in 3 (13%) and pT4 in 3 (13%) patients. In 19 (82.6%) patients, central lymphadenectomy was performed and metastasis was seen in 57%. All patients received RAIT with initial activities of 1.2 (n=1, 4.3%), 2 (n=12, 52.2%) or 3.7 GBq (n=10, 43.5%). Eighteen (78.2%) patients were free of biochemical and radiologic disease at a median follow-up of 60.7 months. Second-line surgery for lymph node relapse was necessary in 3 (13%) cases. There was one disease-associated death. DISCUSSION AND CONCLUSION: Despite high rates of metastasis, most patients were cured, and second-line surgery was rarely required. Further prospective studies are needed to determine whether less aggressive surgical management or omitting adjuvant RAIT are feasible in patients with limited stages at diagnosis.